Desperate deserts - Ganeri, Anita; Phillips, Mike (New York : Scholastic, 2000)
Geography with the gritty bits left in Does geography grind you down? fed up with miserable maps, rotten rock piles and despicable data? Wave goodbye to boring geography lessons as you step onto the scorching sands of Desperate Deserts... Shudder as you're forced to drink camel pee to stay alive. Gasp as a single sand dune on the move buries whole villages. Scream when you come face to face with a deadly rattlesnake. Marvel at the brave desert explorer who trekked to Timbuktu. And if that's not desperate enough for you...find out about the desert where it snows, how to make a tasty pudding from camel milk and why cactus juice could be a deadly drink. Have you got what it takes to survive? It's earth-shatteringly exciting Geography has never been so horrible
Keywords: deserts -- non-fiction